Health-Care Reform in Saudi Arabia: Patient Experience at Primary Health-Care Centers - Mohammed Senitan; James Gillespie (Journal of Patient Experience, 2020)
The aim of this study was to assess the relationship between patients’ demographics, the quality of physician–patient communication, care coordination, and the overall satisfaction rating in primary health-care centers (PHCs). A cross-sectional study was conducted using a patient experience tool. A convenience sample of 157 patients visiting PHCs were retrieved from 10 out of the 13 Saudi regions. A total of 81% of the overall ratings could be attributed to the predictors included in the model. The highest predictor of the overall rating in this model was physicians answering of patient questions, followed by time spent with the physician, type of PHC, and the abilities of the physician to listen carefully, explain things clearly, and show respect. The weakest predictors were follow-up by the health-care provider and physician’s knowledge of the patient’s medical history. Our findings suggest that to improve the overall patient experience and the quality of care at PHCs requires extra attention to physician–patient communication. To improve quality, safety, and efficiency, the Ministry of Health should ensure interpretation service for patients at PHCs either public or private. The Saudi Central Board for Accreditation of Healthcare Institutions should enhance the physician–patient communication as part of their standards for accrediting PHCs.